2016
DOI: 10.4040/jkan.2016.46.6.780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Customized Birth Control Program for Married Immigrant Postpartum Mothers

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0) If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: This study was conducted to develop a customized birth control program and identify its effects on attitude, subjective norm, behavioral control, intention, and behavior of contraception amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…[4,5] Aluminum and silicon are also sometimes used as alloying supplements for high-Mn austenitic TWIP steels to adjust SFE, provide desirable solution strengthening, and suppress delayed fracture. [6][7][8] The alloying design that involves high manganese percentage causes a relatively high cost of the steel production that is one of the main disadvantages of high-Mn TWIP steels.…”
Section: High-mn Structural Steels Have Aroused a Greatmentioning
confidence: 99%
“…[4,5] Aluminum and silicon are also sometimes used as alloying supplements for high-Mn austenitic TWIP steels to adjust SFE, provide desirable solution strengthening, and suppress delayed fracture. [6][7][8] The alloying design that involves high manganese percentage causes a relatively high cost of the steel production that is one of the main disadvantages of high-Mn TWIP steels.…”
Section: High-mn Structural Steels Have Aroused a Greatmentioning
confidence: 99%
“…Kim et al [56] suggested that the fracture mechanisms in TWIP steels are related to martensitic transformation in the presence of residual stresses. This consideration can be accepted for TWIP steels containing less than 1% of Al.…”
Section: Microstructural Study In the Fracture Regionmentioning
confidence: 99%
“…All 10 studies included Vietnamese participants, and the overall proportion of Vietnamese women was largest, followed by those of Chinese (7 studies), Filipino (5 studies), Uzbekistani (1 study), Japanese (1 study), and Cambodian (1 study) women. One study 21 recruited women during the postnatal period, 6 recruited women during the prenatal period, [22][23][24][25][26][27][28] and 2 recruited women who planned to become pregnant. 29,30 Of the studies that recruited women during the prenatal period, 2 involved interventions that lasted beyond birth.…”
Section: Study Characteristicsmentioning
confidence: 99%